The Influence Of Capital Structure, Liquidity, And Leverage On Firm Value With Profitability As An Intervening Variable In Automotive Companies Listed On The Indonesia Stock Exchange (IDX) Period 2019 - 2021 - Arthur Simanjuntak; Yosephine Natalita Sembiring; Thomas Sumarsan Goh; Gracesiela Y Simanjuntak; Nindy L Simanullang (Jurnal Ilmiah Accusi, 2023)
This study aims to examine the impact of capital structure, liquidity, and leverage on firm value while considering profitability as an intervening variable. The independent variables in this study are measured using Debt to Equity Ratio (DER) for capital structure, Current Ratio (CR) for liquidity, and Debt to Assets Ratio (DAR) for leverage. The dependent variable is the firm value, which is measured using Price to Book Value (PBV), and profitability is measured using Return on Assets (ROA) as the intervening variable. The population of this study consists of companies listed on the Indonesia Stock Exchange (BEI) that have published financial reports during the period 2019-2021 in the automotive sector. The sampling method used in this research is census sampling, and a total of 42 data points are analyzed. The results of the analysis indicate that capital structure has a positive impact on firm profitability, while liquidity and leverage do not have a significant influence on profitability. Furthermore, the combined effect of capital structure, liquidity, and leverage does not significantly affect firm value. However, profitability has a positive impact on firm value. Further analysis reveals that capital structure directly affects firm value, while liquidity indirectly affects it through profitability. Moreover, profitability also has a direct impact on firm value. These findings suggest that profitability plays a crucial role in linking the factors of capital structure and liquidity to firm value within the context of the automotive companies in Indonesia. Therefore, the findings of this study provide valuable insights for companies in managing their capital structure and liquidity with the goal of enhancing firm value through improved profitability